2021
DOI: 10.7759/cureus.19940
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Yield and Safety of Bronchoscopic Lung Cryobiopsy in Evaluation of Lung Mass

Abstract: BackgroundA mass lesion in the lung is a common finding seen on chest radiology. The prognosis of patients with mass lesions in the lung is capricious as malignancy is a consideration. It is essential to diagnose the underlying aetiology at the earliest with minimally invasive procedures for prompt treatment of the case. Bronchoscopic lung cryobiopsy (BLC) is a newer interventional technique in pulmonary medicine for the diagnosis of mass lesions in the lung. Materials and methodsThis is a retrospective study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…At least five endobronchial/transbronchial forceps biopsies should be obtained, and an additional five forceps biopsies or two cryo-biopsies could be considered to maximise tissue volume [9]. In a cryo-biopsy, the lung tissue is rapidly frozen prior to removal and the technique allows for larger samples with reduced artefacts compared with other techniques [17]. Cryo-biopsy has most commonly been used for diagnosing interstitial lung disease [25]; however, studies have shown that it is an efficient sampling technique for lung cancer [17,25].…”
Section: Flexible Bronchoscopymentioning
confidence: 99%
See 2 more Smart Citations
“…At least five endobronchial/transbronchial forceps biopsies should be obtained, and an additional five forceps biopsies or two cryo-biopsies could be considered to maximise tissue volume [9]. In a cryo-biopsy, the lung tissue is rapidly frozen prior to removal and the technique allows for larger samples with reduced artefacts compared with other techniques [17]. Cryo-biopsy has most commonly been used for diagnosing interstitial lung disease [25]; however, studies have shown that it is an efficient sampling technique for lung cancer [17,25].…”
Section: Flexible Bronchoscopymentioning
confidence: 99%
“…In a cryo-biopsy, the lung tissue is rapidly frozen prior to removal and the technique allows for larger samples with reduced artefacts compared with other techniques [17]. Cryo-biopsy has most commonly been used for diagnosing interstitial lung disease [25]; however, studies have shown that it is an efficient sampling technique for lung cancer [17,25]. Endobronchial/transbronchial cryo-biopsy may increase histological and molecular detection rates of lung tumours when compared with other tissue sampling methods [26,27], and has been shown to provide a high diagnostic yield (94%) [17].…”
Section: Flexible Bronchoscopymentioning
confidence: 99%
See 1 more Smart Citation